Kesetabilan Emulsi Formulasi Pestisida bentuk Emulsifier Concentrat - Sumingkrat Sumingkrat (Jurnal Kimia dan Kemasan, 1989)
In Indonesia, pesticide formulation mostly used is Emulsifiable Concentrate (EC). In order to get a suitable formulation in application, effective in use, stable in certain period of time and economically, stabilization of emulsion become an important thing. The stabilization is influenced specially by variety and optimum amount of emul sifier used. The Industry has been interested in emulsions stabilized by blends of anionic and nonionic emulsifier.